Psychosocial Impact of Malocclusion and Self-Perceived Orthodontic Treatment Need among Young Adult Dental Patients - Ben Gassem, Afnan A.; Aldweesh, Aljazi H.; Alsagob, Eman I.; Alanazi, Aljawharah M.; Hafiz, Arwa M.; Aljohani, Rahaf S.; Kurdi, Yara E.; Abu Hammad, Osama (European Journal of Dentistry, 2022)
Objectives To investigate the psychosocial impact of malocclusion and self-rated and clinician-rated orthodontic treatment need on young adult patients in the Western Province of Saudi Arabia.Materials and Methods Eighteen- to 30-year-old patients (n=355) attending a tertiary dental care facility were included. Three instruments were used for data collection: (1) Psychosocial Impact of Dental Aesthetic Questionnaire (PIDAQ), (2) aesthetic component of the Index of Orthodontic Treatment Need (IOTN-AC), self-rated and clinician-rated, and (3) clinician-rated Dental Aesthetic Index (DAI). Data analysis included descriptive statistics, Kruskal–Wallis test, Mann–Whitney U-test, and multiple linear regression analysis.Results Females were significantly more impacted than males on all domains with the exception of the dental self-consciousness domain. For both the self-rated and clinician-rated IOTN and the DAI, it was found that the more severe the malocclusion, the higher the impact on all domains except for the dental self-confidence domain, which showed that patients with mild malocclusions were more affected than those with moderate and severe malocclusions. Significant associations were observed between independent variables (age, sex, self-rated IOTN, and DAI) and total PIDAQ score.Conclusions Perceived psychosocial impact of dental aesthetics is directly related to severity of malocclusion (self-rated and clinician-rated) for all domains of the PIDAQ accept the DSC, and females showed higher psychosocial impact than males. Clinicians should consider the impact of malocclusion and certain demographic characteristics on the psychosocial well-being of an individual when determining the orthodontic treatment need.
Keywords: malocclusion; perceptions; oral health-related quality of life; Dental Aesthetic Index; Index of Orthodontic Treatment Need